A Visual Notation for Declarative Behaviour Specification - Kuehne, Thomas (Electronic Communications of the EASST, 2011)
Logical programming has many merits that should appeal to modellers. It enables declarative specifications that are free from implementation details and even (mostly) abstracts away from control flow specification. However, the textual syntax of, for example PROLOG, most likely represents a barrier to the adoption of such languages in the modelling community. The visual notation presented in this paper aims to facilitate the understanding of behaviour specifications based on logic programming. I anticipate that the dataflow-like nature of the resulting diagrams will appeal to modellers. I believe the visual notation to be an improvement over the traditional textual syntax for the purpose of specifying PROLOG programs as such, but the ultimate hope is to have found a vehicle to make declarative logic programming a commonplace activity in multi-paradigm modelling.